Deep and extreme child poverty in rich and poor nations: Lessons from Atkinson for the fight against child poverty - Yixia Cai; Timothy M. Smeeding (Luxembourg Income Study (LIS), 2019)
The paper documents child poverty levels and trends using both relative ('deep') and absolute ('extreme') measures in two clusters: Anglo-Saxon high-income countries and upper middleincome countries. We also investigate the influence of different components of household income and other resources on child deep-poverty rates to examine the role of the market and the redistributive effects that materialize through private transfers, public benefits, and tax systems on generating poverty reduction. Overall, middle-income nations have witnessed continuous reductions in their extreme child poverty rates, while mild decreases or fluctuations have been observed in the five high-income nations, with the U.S. highlighted by its relatively high rates of deep and extreme poverty regardless of absolute or relative measures and type of equivalence scale used. Private institutions play a larger role in poverty reduction in middle-income nations compared to its impact on developed nations. The degree of dependence on universal or assistance benefits varies among high-income nation. In the U.S., universal programs tend to be meager, while Australian social insurance and universal benefit are robust in their fight against deep poverty. Brazil stands out by its overwhelmingly large proportion of social insurance programs that contribute to improvements of its deep child poverty situation, and South Africa's assistance benefit system performs better in lifting children out of deep poverty.
Keywords: I30; I32; I38; 330; Child poverty; Universal benefits; Social assistance; Cross-national comparison